1987
DOI: 10.1007/bf00696368
|View full text |Cite
|
Sign up to set email alerts
|

Blood lactate parameters related to aerobic capacity and endurance performance

Abstract: The relationships among four descriptors of lactate increase: lactate threshold (LT) (the VO2 at which blood lactate concentration begins to increase above the resting level during an incremental exercise test), LT1 (the VO2 at which blood lactate increases 1 mM above the resting level), LT2 (the VO2 at which blood lactate concentration reaches a fixed value of 2 mM), onset of blood lactate accumulation (OBLA; the VO2 at which blood lactate reaches a concentration of 4 mM), were compared with aerobic capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0
3

Year Published

1990
1990
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(93 citation statements)
references
References 28 publications
7
81
0
3
Order By: Relevance
“…Numerous earlier studies reported an association between lactate and ventilatory thresholds and exercise performance (3,19,25,26,50). However, these studies focused on the relationships among direct blood lactate measurements (19,26,50) or indirect methods using gas exchange (3,25), but not between blood-and ventilation-based methods and exercise performance. Moreover, these associations have not been thoroughly explored in hot or cool environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous earlier studies reported an association between lactate and ventilatory thresholds and exercise performance (3,19,25,26,50). However, these studies focused on the relationships among direct blood lactate measurements (19,26,50) or indirect methods using gas exchange (3,25), but not between blood-and ventilation-based methods and exercise performance. Moreover, these associations have not been thoroughly explored in hot or cool environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have aimed to compare different methods to determine the lactate and ventilatory thresholds using different protocols (9,11,35,40), although it is difficult to draw conclusions, as the results heavily depend on the specific methodologies used (e.g., cycle or treadmill, duration of exercise stage, blood sampling site). Others have attempted to investigate the relationship between lactate or ventilatory threshold and exercise performance in thermoneutral conditions (6,19,50). However, these studies commonly fail to standardize the comparisons to a specific environmental condition (laboratory vs. field) or activity (treadmill vs. road running) when comparing lactate or ventilatory threshold with exercise performance.…”
mentioning
confidence: 99%
“…B l o o d l a c t a t e c o n c e n t r a t i o n ( L A ) d u r i n g submaximal exercise is closely related to aerobic capacity, especially, lactate threshold (LT) and OBLA (Onset of Blood Lactate Accumulation) are indicators of aerobic capacity better or at least no worse than V ・ of aerobic capacity better or at least no worse than ・ of aerobic capacity better or at least no worse than O 2 max [Yoshida et al, (1987) ; Tokmakidis et al, (1998)]. Because LT in particular can be measured in light to moderate submaximal exercise, it has possibilities for safe and accurate evaluation, in older people.…”
Section: Introductionmentioning
confidence: 99%
“…As lactate accumulation/removal ratio is considered a good marker of aerobic capacity [58,59], we subjected all mice at 4 months of age to a 28-minute constant load test (at 85% of the maximal speed reached during the incremental test) and measured the lactate accumulation in the bloodstream every 7 minutes (Figure 2(a)). WT mice displayed a typical lactate accumulation curve, increasing from baseline (0.09 ± 0.30 mmol/L) to a peak at the 14th minute of 2.87 ± 0.90 mmol/L, followed by a plateau.…”
Section: Aerobic Training Increased Functional Output Andmentioning
confidence: 99%